STUDI SANITASI LINKUNGAN MASYARAKAT DI KANAGARIAN TERAKAK TEMPATIH IV KOTO MUDIK KEAMATAN BATANG KAPAS PESISIR SELATAN - Efrianti, Nova; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
Nova Efrianti (2013): Study of Community Environmental Sanitation in Kenagarian hovel Tempatih District IV Koto Homecoming Trunk Cotton South Coastal District.This study aims to find out about the data and discussion are: 1. Healthy Latrine access, 2. Wastewater Management, 3. Household Waste Management. The descriptive research method. Descriptive research that is intended to make plans about situations or events that are related. Location of this study was all the people in the hut Kenagarian Tempatih IV Koto Homecoming Representative to obtain data, the research ellipse in the hut, Bunga Tanjung, and Padang Galundi. Sampling was done by the method: proportional random sampling, 15% of 603 people is as much as 90 respondents. Based on data collection and interpretation of data, can be summarized as follows: 1. Seen from healthy latrine access, many people still do not use latrines healthy. People still use rivers and streams to be made in place of the water disposal is 65.55%, 2. Seen from domestic waste water management, there are still many people dispose sewage water kesembarang place at 56.66%, and sebagiaan String together an aperture in the former reservoir for water toilets, 3. In the management of the household waste they do not know how to mana